Sumoylation of the Rad1 nuclease promotes DNA repair and regulates its DNA association - Sarangi, Prabha; Bartosova, Zdenka; Altmannova, Veronika; Holland, Cory; Chavdarova, Melita; Lee, Sang Eun; Krejci, Lumir; Zhao, Xiaolan (Nucleic acids research, 2014)
The Saccharomyces cerevisiae Rad1-Rad10 complex is a conserved, structure-specific endonuclease important for repairing multiple types of DNA lesions. Upon recruitment to lesion sites, Rad1-Rad10 removes damaged sequences, enabling subsequent gap filling and ligation. Acting at mid-steps of repair, the association and dissociation of Rad1-Rad10 with DNA can influence repair efficiency. We show that genotoxin-enhanced Rad1 sumoylation occurs after the nuclease is recruited to lesion sites. A single lysine outside Rad1's nuclease and Rad10-binding domains is sumoylated in vivo and in vitro. Mutation of this site to arginine abolishes Rad1 sumoylation and impairs Rad1-mediated repair at high doses of DNA damage, but sustains the repair of a single double-stranded break. The timing of Rad1 sumoylation and the phenotype bias toward high lesion loads point to a post-incision role for sumoylation, possibly affecting Rad1 dissociation from DNA. Indeed, biochemical examination shows that sumoylation of Rad1 decreases the complex's affinity for DNA without affecting other protein properties. These findings suggest a model whereby sumoylation of Rad1 promotes its disengagement from DNA after nuclease cleavage, allowing it to efficiently attend to large numbers of DNA lesions.
Keywords: Saccharomyces cerevisiae Proteins; poškození DNA; protein-serin-threoninkinasy; intracelulární signální peptidy a proteiny; mutace; DNA Damage; Endonucleases; Protein Serine-Threonine Kinases; Sumoylation; Intracellular Signaling Peptides and Proteins; sumoylace; Ubiquitin-Protein Ligases; ubikvitinligasy; Lysine; lysin; DNA Repair; oprava DNA; endonukleasy; enzymy opravy DNA; Saccharomyces cerevisiae - proteiny; DNA; Mutation; DNA Repair Enzymes